MANAGEMENT POLICY IMPLEMENTATION WASTE AT CIMENTENG TPA SUKABUMI DISTRICT - Hariyadi, Barlian; Purwanti, Dian; Basori, Yana Fajar FY (DIA: Jurnal Administrasi Publik, 2023)
This research is entitled "Implementation of Waste Management Policy at TPA Cimenteng, Sukabumi Regency". The purpose of this study is to find out what the implementation of waste management policies is like at the Cimenteng TPA, Sukabumi Regency and the inhibiting factors in its implementation. This study uses a qualitative method with a phenomenological approach. The informants in this study were the Sukabumi Regency Housing and Settlement Office, the Head of TPA Cimenteng, and the community in the TPA Cimenteng environment. The validity of the data in this study used source triangulation, technical triangulation, and member checking methods. The results of this study indicate that waste management at Cimenteng TPA has been running but has not fully run optimally, this is shown by mountains of garbage that are not managed properly, tools that are often damaged, this clearly disrupts activities at Cimenteng TPA, for the inhibiting factor is . The lack of budget for Cimenteng TPA so as to repair or rejuvenate existing equipment at Cimenteng TPA has caused waste management at Cimenteng TPA to not run optimally. In addition, in 2019 Indonesia was hit by the Covid outbreak, the government finally cut the budget for handling Covid. The lack of budget for Cimenteng TPA so as to repair or rejuvenate existing equipment at Cimenteng TPA has caused waste management at Cimenteng TPA to not run optimally. In addition, in 2019 Indonesia was hit by the Covid outbreak, the government finally cut the budget for handling Covid. The lack of budget for Cimenteng TPA so as to repair or rejuvenate existing equipment at Cimenteng TPA has caused waste management at Cimenteng TPA to not run optimally. In addition, in 2019 Indonesia was hit by the Covid outbreak, the government finally cut the budget for handling Covid.